Studi Anther Tanaman Tebu (Saccharum officinarum L.) sebagai Tanaman Donor Kultur Mikrospora - Anitasari, Septarini Dian; Astarini, Ida Ayu; Defiani, Made Ria (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2022)
Sugarcane is an economically valuable plant that continues to be developed to produce superior varieties, the technique to get new varietis used is microspore culture biotechnology. There are many obstacles in the implementation of the microspore cultivar method. Therefore, in this research, a study of sugarcane anthers was carried out. This research used sugarcane panicles for anther selection and then observed under a microscope. Data is analyze with descriptivey method. The results show that white and yellow anthers are the right materials for microspore culture donors